The Impact of Influencer Marketing on Beauty Product Purchase Decisions among Generation Z - Sucidha, Irma (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to understand the impact of comment-based engagement in influencer marketing on purchasing decisions for beauty products among Generation Z. Using a systematic literature review method, this study analyzes relevant literature to identify the effects of various types of engagement, both positive and negative, in shaping perceptions. consumers and influence purchasing intentions. Research results show that positive comments from influencers increase brand trust and encourage consumer loyalty, while negative comments often have a negative impact on brand image, reduce purchase intentions, and even potentially trigger product boycotts. The theoretical implications of this research include enriching digital marketing theory through exploring comment-based engagement dimensions. In practical terms, these findings provide guidance for marketers in utilizing influencer marketing strategies more effectively, through an approach that considers the quality of engagement and proactive responses to negative comments. This research also offers suggestions for beauty industry players to increase campaign effectiveness by minimizing the reputational risk of negative comments and optimizing the influence of positive comments. Limitations of this research include the limited coverage of social media platforms and limitations on observational studies, as well as opening opportunities for further research through experimentation and exploration of different platforms.